A Digest of the Ordinances of the Corporation of the City of Philadelphia, at 87, Firing of Guns, &c., Act of April 9, 1760, § 7. (1828) - (:unkn) unknown (My University, 1760)
No person whatsoever shall presume to shoot at, or kill with a fire arm, any pigeon, dove, partridge, or other fowl, in the open streets of the city of Philadelphia, or in the gardens, orchards and inclosures, adjoining upon and belonging to any of the dwelling-houses within the limits of the said city, or suburbs thereof, or any of the boroughs or towns within this province,
Keywords: HUNTING REGULATION